Narrative Values, the Value of Narratives - Baetens, Jan; Caracciolo, Marco; Godioli, Alberto; Harbers, Frank; Herman, Luc; Iversen, Stefan; Kiss, Miklós; Korthals, Liesbeth; Meretoja, Hanna; Moenandar, Sjoerd-Jeroen; Moenandar, Sjoerd-Jeroen; O'Connor, Emma Frances; et al. (Narratologia : Contributions to Narrative Theory ,, 2024)
There is a growing interest in studying narrative discourse as 'experimental values laboratory,' both reflecting social values and participating in their circulation. Given the omnipresence of narrative and story-telling practices in public life, from advertising to politics, law, and the media, the need for narrative savviness - that is, the ability to read for the values that inhere in and are transmitted through narrative - transcends the study of fiction. This volume brings into focus the ways in which narratives are informed and shaped by values, and how they transmit values themselves. The authors in the volume take a broad range of approaches to narrative, including narratology, rhetoric, ecocriticism, narrative (meta)hermeneutics, applied narratology, and frame theory. By bringing together strands of contemporary narrative theory that are not often found in dialogue with one another, the volume aims to capture the most recent developments in the study of narrative ethics.